SISWA YANG KECANDUAN GAME ONLINE DAN PERILAKU AGRESIF DI SMP NEGERI 14 PEKANBARU - Pratiwi, Rika R iyana; Yakub, Elni; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The phenomenon that occurs in the field shows the much of students who play online games. Online games can make a person become addicted. Students who play online games tend to have aggressive behavior such as rude said. The purpose of this research are: 1) to know the description of the students who are addicted to online game, and 2) to know the description of aggressive behavior of students who are addicted to online game. The population of this study are students of class VII consisting of 7 classes. A sample of 65 students. The sampling technique is purposive sampling. This research is quantitative descriptive. The data collection instrument uses a questionnaire which is then analyzed by grouping the data and calculating the percentage. The results of this study indicate the duration of addiction time online game is for 3-4 hours a day and ignore to other activity; where online game play is generally done is at home; the types of online games favored by students are Mobile Legends (ML) and Defense of the Ancients (DotA) 2; students who are addicted to online games have health problems like eye pain; psychological conditions experienced by students easily irritated; from the aspect of student learning constantly think of online games during learning; from the social adjustment aspects students ignore others. Whereas the aggressive behavior of students who are addicted to online games including physical aggression are exposed through a tendency to hit if hit by someone then it will retaliate with a harder blow; and commonly performed verbal aggression is to threaten by issuing harsh wordKeywords: Addiction of online games, Aggressive behavior